2020
DOI: 10.1089/acm.2019.0250
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Yoga Practice in Cardiac Rehabilitation Program: A Randomized Control Trial

Abstract: Background: Coronary artery disease (CAD) is a detrimental noncommunicable disease, which is increasing due to sedentary lifestyle and urbanization in the young population. It is further elevated with risk factors such as stress, anxiety, depression, an increase in triglycerides, dyslipidemia, hyperglycemia, hypertension, and so on, which manifests as atherosclerotic disease. Yoga-based lifestyle intervention is a noninvasive effective treatment method to control and prevent cardiac risk factors in CAD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In total, 260 participants in five randomized controlled studies (16,17,(26)(27)(28) evaluated the effect of exercise therapy on anxiety in patients with coronary heart disease (Figure 4). Using evaluation methods, including GAD7, HADS-A, HAMA, and DASS-A, due to the diversity of dimensions, we used SMD to aggregate the anxiety symptom data, and the fixed-effect model was chosen because the combined results had no obvious statistical heterogeneity.…”
Section: Primary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 260 participants in five randomized controlled studies (16,17,(26)(27)(28) evaluated the effect of exercise therapy on anxiety in patients with coronary heart disease (Figure 4). Using evaluation methods, including GAD7, HADS-A, HAMA, and DASS-A, due to the diversity of dimensions, we used SMD to aggregate the anxiety symptom data, and the fixed-effect model was chosen because the combined results had no obvious statistical heterogeneity.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…The results showed that compared with the control group, the intervention group had a significant overall effect in improving anxiety of patients with coronary heart disease. Since one of the trials did not study the target outcome of depression and could not be included in the meta-analysis, 731 participants in 10 randomized controlled studies (16,17,(20)(21)(22)(23)(24)(25)(26)(27) evaluated the effect of exercise therapy on depression in patients with coronary heart disease (Figure 5). Using evaluation methods, including HAMD, SDS, PHQ-9, BDI, CDS, HADS-D, CDS, and DASS-D, the random effects model was chosen because the combined results were highly statistically heterogeneous.…”
Section: Primary Outcomesmentioning
confidence: 99%
“… 12-month LVEF improved in yoga group ( p =0.001) in those with LVEF <53% LVEF 47% to 53% at 1 year vs 49% in control. Significant difference in weight loss in those with BMI >23 ( p =0.038) Total cholesterol p =0.61 Total triglycerides p =0.03 Total HDL p =0.003 Total LDL p =0.75 Total VLDL p =0.03 PSS p =0.12 PANAS-positive p =0.02 PANAS-negative p=0.97 HADS-Anxiety p =0.42 HADS-Depression p =0.07 Sharma et al 14 2020 India Single centre CAD – Medically managed MI with LVSD 66 (33:33) 12-week yoga-based cardiac rehab adjunct Standard care (not exercise-based) 3 months LVEF Biochemical: Total triglycerides, cholesterol, LDL, HDL QOL: DASI and MET Anxiety and depression: HAM-A CDS No difference in LVEF ( p =0.218) No difference in biochemical measures Statistically significant improvement in QOL ( p <0.001) And anxiety and depression ( p <0.001) Tillin et al 16 2019 UK Multicentre ACS 60 (25:35) Addition of at least 18 yoga classes to standard programme Control – standard UK NHS cardiac rehab programme Exercise-based CR 3 months Filling pressures (E/e’) 6MWT BP HR blood profile QOL E/e’ p =0.4 6MWT p =0.7 Resting SBP p =0.5 Resting DBP p =0.6 Resting HR p =0.8 International physical activity score p =0.8 EQ-5D health status p =1.0 EQ-5D self-rated thermometer p =0.6 PSS p =0.11 Abbreviations : ACS, acute coronary syndrome; BMI, body mass index; CABG, coronary artery bypass graft; CAD, coronary artery disease; CDS, Cardiac Depression Scale; CR, cardiac rehabilitation; DASI, Duke Activity Status Index; DBP, diastolic blood pressure; HADS, Hospital Anxiety and Depression Score; HAM-A, Hamilton Anxiety Rating Scale; LVEF, left ventricular ejection fraction; LVSD, left ventricular systolic dysfunction; MACE, major advers...…”
Section: Resultsmentioning
confidence: 97%
“… 12 One study only looked at patients post-CABG (Raghuram et al), and one study only looked at MI patients receiving medical therapy (Sharma et al), which is not reflective of current practice. 13 , 14 Control group intervention also varied between studies ranging from purely pharmacological intervention to comprehensive exercise-based programmes. There were high numbers screened out in the studies, and dropout rates varied from 40% to almost nothing (Sharma et al).…”
Section: Resultsmentioning
confidence: 99%
“…Today, yoga is used as a treatment for various conditions such as hypertension, multiple sclerosis, asthma, low back pain, and arthritis, as well as pain and stress management. The results of various studies have shown that doing yoga exercises in women with polycystic ovary syndrome has led to improved insulin sensitivity and lipid indexes [ 16 19 ]. Furthermore, in the latest systematic review studies conducted in 2020, it was stated that although regular exercises have helped improve hormonal, metabolic, and clinical parameters among these patients, there is the need for better and more accurate studies in this regard [ 8 ].…”
Section: Introductionmentioning
confidence: 99%